ECOTOURISM AND RURAL TOURISM THE MAIN REASONS WHY RURAL LOCAL COMMUNITIES DEPEND ON ECOTOURISM (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Nowadays, ecotourism has been one of rapidly growing tourism industries, so category principles are beginning to spread more at the regional level. Rural places are rich in ecological and rural areas. For a long time in their existence, rural societies have depended on the abundance of natural resources. However, in the 20th century, main alteration in technology, political or economic causes have caused a profound transformation in agriculture, as well as other industrial resources were renewable, which has directed rural communities to be dependent on their face. For rural destinations, the fast stage of alteration has caused with it not only chances but also serious difficulties. This approach also causes valuable chances for developing the competitiveness of local businesses.